Two New Species of the Genus Thoracophorus Motschulsky, 1837 (Coleoptera: Staphylinidae, Osoriinae) with Remarks on Ecology of the Genus in the Neotropical Region - Ulrich Irmler (Psyche: A Journal of Entomology)
The new species Thoracophorus venezuelanus and T. silvaticus are described. The ecological information from labels and that produced by more detailed studies in Central Amazonia indicate that tree canopies and tree trunks are main habitats of Thoracophorus species, and that many species might be associated with ants or termites.